2015
DOI: 10.3390/v7082847
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Control of Salmonella Enteritidis in Foods Using Bacteriophages

Abstract: Two lytic phages, vB_SenM-PA13076 (PA13076) and vB_SenM-PC2184 (PC2184), were isolated from chicken sewage and characterized with host strains Salmonella Enteritidis (SE) ATCC13076 and CVCC2184, respectively. Transmission electron microscopy revealed that they belonged to the family Myoviridae. The lytic abilities of these two phages in liquid culture showed 104 multiplicity of infection (MOI) was the best in inhibiting bacteria, with PC2184 exhibiting more activity than PA13076. The two phages exhibited broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 38 publications
(42 reference statements)
11
98
1
1
Order By: Relevance
“…In some cases, PEG precipitation is applied in the concentration of phage particles procedure. It was used to prepare high titers of Salmonella-specific phages by Bao et al (2011), Wong et al (2014, Bao et al (2015) and other researchers.…”
Section: Enumeration Concentration and Purification Of Bacteriophagesmentioning
confidence: 99%
See 3 more Smart Citations
“…In some cases, PEG precipitation is applied in the concentration of phage particles procedure. It was used to prepare high titers of Salmonella-specific phages by Bao et al (2011), Wong et al (2014, Bao et al (2015) and other researchers.…”
Section: Enumeration Concentration and Purification Of Bacteriophagesmentioning
confidence: 99%
“…A novel cold-active bacteriophage VNPH-1 specific for Aeromonas sobria was comparatively stable at pH 5.0 to 10.0 and the optimum phage infectivity occurred at pH 9.0 (Ji et al, 2015). Similarly, Salmonella-infecting bacteriophages REVIEW include phage PA13076 (Bao et al, 2015), phage SE2 (Tiwari et al, 2013), phage PSPu-95 and phage PSPu-4-116 (Bao et al, 2011), were relatively stable within the pH range of 4.0 to 10.0. However, recent studies by Hu et al (2016) on thirteen lytic distinct Pseudomonas bacteriophages reported that all phages were active over a very narrow pH range, from 6.0 to 7.0.…”
Section: Properties Of Bacteriophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Typhimurium) and Escherichia coli ( E. coli ) O157:H7 are major food-borne pathogens causing serious diseases (1, 2). Bacteriophages have been used to bio-control agents in a variety of foods (3, 4). We report a new virulent bacteriophage GG32 isolated from the Guem River in the Republic of Korea.…”
Section: Genome Announcementmentioning
confidence: 99%